STRATEGI GURU BAHASA INDONESIA DI KELAS 1 SMP PENCAWAN MEDAN DALAM MENINGKATKAN LITERASI BACA SISWA (Sindoro: Cendikia Pendidikan, 2025)
This study aims to describe the strategies implemented by Indonesian language teachers to improve reading literacy among first-grade students at SMP Pencawan Medan. Reading literacy is a fundamental skill essential for academic success and the development of critical thinking. This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings indicate that teachers apply several strategies, including a 15-minute reading routine before lessons, the provision of a classroom reading corner, guided reading activities and text discussions, creative literacy assignments, and the use of digital media. These strategies have proven effective in enhancing reading interest, text comprehension, and students’ active engagement in reading activities. The success of these strategies is supported by the teacher’s creativity and a conducive learning environment. These findings are expected to serve as a reference for developing literacy programs at the junior high school level